A review of healthy bars - purchasing motives & challenges: towards Halalan Toyyiban approach - Mohd Noor, Nurul Auni; Hazahari, Noor Yuslida; Shahidan, Norshazila (INHART, IIUM, 2021)
Healthy bars come in various shapes and sizes, each catering to a particular group of people. A detailed guideline and information available will help customers choose and decide which healthy bars suit them and their activities the most. The research of healthy bar's functional properties has been receiving much attention too recently. The latest study aims to explain these different healthy bars and their typical ingredients used in producing them. This review article compares different healthy bars that influence consumers' purchasing motives and elaborates on obstacles producers encounter while producing these healthy bars. Manufacturers of healthy bars commonly encounter numerous challenges, which will be extensively discussed here. The review was carried out by going through 98 publications and extracting information related to four types of nutritious bars: (i) cereal-based bars, (ii) energy bars, (iii) fruit-based bars and (iv) vegetable-based bars. Meanwhile, the packaging attribute is the most crucial component influencing consumers' decisions to buy a healthy bar. Manufacturers discovered the most challenging task: keeping up with the ever-changing demand for unique ingredients in healthy bars and not forgetting their approach in choosing halalan toyyiban food products.